Análisis gramatical del contenido informativo emitido por las redes sociales (no oficiales) Facebook, Instagram y TikTok de la UEB, frente a la calidad de redacción informativa, periodo enero-mayo 2025 - Torres Pinzón, Mileny Nicole (2025)
The purpose of this research was to establish the quality of news writing through the grammatical analysis of news content posted on the unofficial social media platforms Facebook, Instagram, and TikTok of the UEB, between January and May 2025. The study was based on the hypothesis that the grammatical structures in such materials significantly affect the quality of news writing. To conduct the study, a mixed-method approach was used, integrating qualitative and quantitative techniques to gain a comprehensive understanding of the phenomenon. Surveys and interviews were conducted, and a content analysis matrix was developed to examine messages on social platforms. The findings of this research allowed us to detect the frequency of grammatical and spelling errors in news material. The results of this analysis suggest that the way we communicate on social platforms displays specific features that deviate from conventional writing styles, affecting both the form and comprehension of the content. Based on these observations, my thesis proposal suggests writing and grammatical methods that seek to improve the effectiveness of messages on social platforms.